(untitled) (Web of Teachers: Inderscience Research, 2025)
Teaching intercultural communication is incredibly imperative for several reasons, especially in today’s globalized world. As societies become more interconnected, understanding how people from different cultural backgrounds communicate is essential in fostering effective relationships and communication. Thus, teaching intercultural communication in a classroom requires practical applications, and interactive activities to engage students and help them understand cultural differences in communication.